2010
DOI: 10.1186/1471-244x-10-75
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of switching antipsychotic medications in the treatment of schizophrenia

Abstract: BackgroundTo identify patient characteristics and early changes in patients' clinical status that best predict subsequent switching of antipsychotic agents in the long-term treatment of schizophrenia.MethodsThis post-hoc analysis used data from a one-year randomized, open-label, multisite study of antipsychotics in the treatment of schizophrenia. The study protocol permitted switching of antipsychotics when clinically warranted after the first eight weeks. Baseline patient characteristics were assessed using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
31
4
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 52 publications
(53 reference statements)
8
31
4
1
Order By: Relevance
“…These findings are in line with previous reports [14, 15, 23, 24]. The mean daily doses of ZIP were approximately 140 mg in both groups according to recommended and widely used doses of ZIP [25, 26].…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in line with previous reports [14, 15, 23, 24]. The mean daily doses of ZIP were approximately 140 mg in both groups according to recommended and widely used doses of ZIP [25, 26].…”
Section: Discussionsupporting
confidence: 92%
“…In the univariate analysis, older age13,25,27,47,48 and male gender28,44,46 predicted antipsychotic continuation. The primary findings in the multivariate analysis were also consistent with previous research on predictors of medication continuation: longer duration of illness,45 higher baseline HRQOL,58 higher baseline negative symptoms,58 and lower baseline positive symptoms59 have all been identified as predictors of antipsychotic continuation. Interestingly, in one study, lower baseline positive symptoms were reported to predict discontinuation rather than continuation 48.…”
Section: Discussionsupporting
confidence: 86%
“…2003; Broekema et al . 2007; Barnes and Paton, 2011] or switch to other AAPs to optimize symptomatic control [Nyhius et al . 2010].…”
Section: Introductionmentioning
confidence: 99%